Influence of bioadhesive polymers on the protective effect of fluoride against erosion - Ávila, Daniele Mara da Silva [UNESP]; Zanatta, Rayssa Ferreira [UNESP]; Scaramucci, Tais; Aoki, Idalina Vieira; Torres, Carlos Rocha Gomes [UNESP]; Borges, Alessandra Bühler [UNESP] (Elsevier, 2017)
Objective This study investigated if the incorporation of the bioadhesive polymers Carbopol 980, Carboxymethyl cellulose (CMC), and Aristoflex AVC in a fluoridated solution (NaF–900 ppm) would increase the solution's protective effect against enamel erosion. Methods Enamel specimens were submitted to a 5-day de-remineralization cycling model, consisting of 2 min immersions in 0.3% citric acid (6x/day), 1 min treatments with the polymers (associated or not with fluoride), and 60 min storage in artificial saliva. Ultrapure water was used as the negative control and a 900 ppm fluoride solution as positive control. The initial Knoop microhardness (KHN1) was used to randomize the samples into groups. Another two microhardness assessments were performed after the first (KHN2) and second (KHN3) acid immersions, to determine initial erosion in the first day. The formula: %KHNalt = [(KHN3-KHN2)/KHN2]*100 was used to define the protective effect of the treatments. After the 5-day cycling, surface loss (SL, in μm) was evaluated with profilometry. Data were analyzed with 2-way ANOVA and Tukey's tests (p < 0.05). Results For %KHNalt, the polymers alone did not reduce enamel demineralization when compared to the negative control, but Carbopol associated with NaF significantly improved its protective effect. The profilometric analysis showed that Carbopol, associated or not with NaF, exhibited the lowest SL, while CMC and Aristoflex did not exhibit a protective effect, nor were they able to improve the protection of NaF. Conclusions It is concluded that Carbopol enhanced NaF's protection against initial erosion. Carbopol alone or associated with NaF was able to reduce SL after several erosive challenges. Clinical significance Carbopol by itself was able to reduce the erosive wear magnitude to the same extent as the sodium fluoride, therefore, is a promising agent to prevent or control enamel erosion.
Keywords: Dental erosion; Enamel; Fluoride; Microhardness; Polymers; Profilometry